Tax Avoidance, Tax Incentives and Tax Compliance During the Covid-19 Pandemic: Individual Knowledge Perspectives - Indah Hapsari; Supriyati Supriyati (Journal of Accounting and Strategic Finance, 2021)
The COVID-19 pandemic that occurred in early 2020 caused a decrease in the turnover or income of individual taxpayers. Tax avoidance and tax incentives are considered a strategy by taxpayers to reduce tax payments and manage their funds, especially during this pandemic. The condition of the Taxpayer certainly affects the fulfillment of his tax obligations. On the other hand, taxpayer compliance will have an impact on state revenues. Individual taxpayer perspectives on aspects of accounting and taxation knowledge are important to realize the level of taxpayer compliance. This study also relates the efforts of tax avoidance and government tax incentives as mediating variables. The sample data obtained were 131 individual entrepreneur taxpayers who took advantage of tax incentives in Surabaya and its surroundings. The regression test results showed that accounting and taxation knowledge affect tax avoidance efforts, tax incentives, and taxpayer compliance. The results of the Sobel test show that tax avoidance and tax incentives can mediate the impact of accounting and taxation knowledge on taxpayer compliance. The test results of control variables (gender, education, training, length of business, number of employees, business turnover) showed no effect on taxpayer compliance.